2009
DOI: 10.1517/14740330903117271
|View full text |Cite
|
Sign up to set email alerts
|

Risk of venous thromboembolism due to antipsychotic drug therapy

Abstract: An increasing number of reports suggest a link between venous thromboembolism (VTE) and the use of antipsychotics. To better understand this association the available body of evidence has been critically scrutinised. Relevant articles were identified in the databases Scopus and PubMed. Several observational studies using different methodologies show an increased risk of VTE in psychiatric patients. This elevated risk seems to be related to the use of antipsychotic medication and in particular to the use of clo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
45
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 83 publications
(104 reference statements)
3
45
0
Order By: Relevance
“…Since 1953, sporadic case reports and case series have suggested that conventional APD use is an independent risk factor for VTE. 5 In a nested case-control study, Zornberg and Jick 6 demonstrated that current exposure to conventional APDs significantly increases the risk of idiopathic VTE (odds ratio [OR], 7.1; confidence interval [CI], 2.3Y21.9). Kamijo et al 7 studied 16 patients with idiopathic acute pulmonary thromboembolism (mean age, 56), of whom 6 (44%) used conventional antipsychotic drugs; and 1 patient, risperidone.…”
mentioning
confidence: 99%
“…Since 1953, sporadic case reports and case series have suggested that conventional APD use is an independent risk factor for VTE. 5 In a nested case-control study, Zornberg and Jick 6 demonstrated that current exposure to conventional APDs significantly increases the risk of idiopathic VTE (odds ratio [OR], 7.1; confidence interval [CI], 2.3Y21.9). Kamijo et al 7 studied 16 patients with idiopathic acute pulmonary thromboembolism (mean age, 56), of whom 6 (44%) used conventional antipsychotic drugs; and 1 patient, risperidone.…”
mentioning
confidence: 99%
“…In addition, patients who are on antipsychotic medications are at an increased risk of venous thromboembolism [31]; the relationship has been highlighted mostly with clozapine and low-potency first-generation antipsychotics [31].…”
Section: Antipsychoticsmentioning
confidence: 99%
“…In several studies, psychiatric disorders and the medications used for them are also accused of the development of DVT. The increased risk of DVT in patients who are treated with antipsychotic drugs has been reported in several cases [8]. Clozapine is noticeably the most mentioned drug with thromboembolic complications, but olanzapine is also subject to many reports [9].…”
Section: Introductionmentioning
confidence: 99%